Cartografia do expressionismo na literatura de língua portuguesa - Gomes, Alexandre Rodrigues (2018)
ABSTRACT The theme of this research explores inter-art studies, relating literature, theater and cinema in order to investigate examples of Expressionist aesthetics in literature written in Portuguese language, based on the critical study of two plays by the Portuguese writer Raul Brandão (1867-1930): O Gebo e a Sombra (1923) and O Avejão: EpisódioDramático (1929), and two plays by the Brazilian writer Nelson Rodrigues (1912-1980): Vestido de Noiva (1943) and Valsa no6 (1951). Additionally, the impact of Expressionist aesthetics on film art from the 1920s to the early 21st century will be also be explored beased on such theorists as Roger Cardinal, R.S. Furness and Lotte H. Eisner. Finelly, approaching Raul Brandão's theater, this research will also feature the reflections of such scholars as VítorViçoso, Eduardo Lourenço and Otto Maria Carpeaux, as well as several other whose articles on the Portuguese writer were collected and organized in a book by Otávio Rios Portela. As for Nelson Rodrigues's dramaturgy, besides SábatoMagaldi's studies, Eudinyr Fraga's findings on Expressionist resources in work of Rodrigues will be fundamentally important. Although Expressionism is the axis that crosses and guides this research, other topics equally relevant to the understanding of work and thinking of these two authors will also be explored. Keywords: Expressionism. Literature. Cinema. Raul Brandão. Nelson Rodrigues.